6(c-2)+9=3+c-6

Simple and best practice solution for 6(c-2)+9=3+c-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(c-2)+9=3+c-6 equation:


Simplifying
6(c + -2) + 9 = 3 + c + -6

Reorder the terms:
6(-2 + c) + 9 = 3 + c + -6
(-2 * 6 + c * 6) + 9 = 3 + c + -6
(-12 + 6c) + 9 = 3 + c + -6

Reorder the terms:
-12 + 9 + 6c = 3 + c + -6

Combine like terms: -12 + 9 = -3
-3 + 6c = 3 + c + -6

Reorder the terms:
-3 + 6c = 3 + -6 + c

Combine like terms: 3 + -6 = -3
-3 + 6c = -3 + c

Add '3' to each side of the equation.
-3 + 3 + 6c = -3 + 3 + c

Combine like terms: -3 + 3 = 0
0 + 6c = -3 + 3 + c
6c = -3 + 3 + c

Combine like terms: -3 + 3 = 0
6c = 0 + c
6c = c

Solving
6c = c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
6c + -1c = c + -1c

Combine like terms: 6c + -1c = 5c
5c = c + -1c

Combine like terms: c + -1c = 0
5c = 0

Divide each side by '5'.
c = 0

Simplifying
c = 0

See similar equations:

| 1.4-0.4x=5.2 | | 2*(7x+2)+12*(x+1)=12 | | 10-x=-13 | | X^2-x+17=0 | | X/2-(x-1/3)=1/9 | | -[10z-(14z+9)]=9+(3z+3) | | 6x-3=91 | | 40-3(2w+1)=11w-3(11+w) | | 3+x=117 | | x^3-2x^2+7x-14=0 | | 66/22r+(16/16-1)=r+(72/3/3) | | tanx=2sinx | | -1(3-4)+1x^2= | | 9s-5q=-4u | | n+9/3=44/9 | | 2+x=120 | | 2(7x+2)+12(x+1)=12 | | 25xsquared-20x+4=0 | | 4-4(1+-4x)=32 | | 5/6(2y+4)=10 | | 4n-10=5n-6 | | n+9/2=44/9 | | cos^2(x)=cosx | | 5-x=3x+9 | | 9-3x-1=6x+10 | | x/(x+3)=(x-4)/3 | | x^3/15 | | 8+(11/p)=10/p^2 | | 3y-y=-16 | | 4-4(1-4x)=32 | | 2x+2=314 | | 1-2n=n-14 |

Equations solver categories